"Mining is in the belly": The pursuit of individual wealth in Rwanda. (October 2019) - Perks, Rachel
Abstract: This paper examines the socio-economic conditions under which Rwandan men moved into artisanal and small-scale mining (ASM), and highlights the personal progress made possible through their labour. In the face of an unforgiving rural environment and an economy limiting in labour opportunity, young men leave their family homesteads in search of off-farm employment. Though these men never associate their labour migration with poverty, their stories are laden with reference to the "better life" they have achieved by working in the mines. Their stories show how mining is an over-looked solution to the long-held puzzle confounding underemployment and bleak non-farm opportunities in rural Rwanda. Highlights: Use of life history method to analyse wealth creation in mining in Rwanda. 19 male miners' life histories gathered across seven mine sites in 2012. Between them, miners spent on average 37.3 years in mining, the longest serving 59 years and the shortest serving 14 years. Life in mining provides a pathway out of economic and social constraint for miners interviewed when analysed against prior poverty frameworks developed for rural Rwanda.